FACTORS ASSOCIATED WITH ONGOING TRAUMATIC BRAIN INJURY-RELATED SYMPTOMS AMONG FEMALE OFFENDERS. (7th October 2012) - Pickelsimer, E; Ferguson, P; Cornelius, M
Abstract : Background: Ongoing traumatic brain injury (TBI)-related symptoms, post-traumatic stress disorder (PTSD), and substance dependency (SuD) can greatly affect an offender's ability to function while incarcerated and upon community reentry. Aims/Objectives/Purpose: To identify factors associated with ongoing TBI-related symptoms among female offenders. Methods: 275 female offenders were asked whether they experienced any of 19 ongoing symptoms after TBI. Variables (aggression, PTSD, mental health treatment, SuD, childhood victimisation, lack of parental/caregiver support, intimate partner violence, free or reduced lunch (ie, SES proxy) were entered into a Robust Poisson model (p≤0.25) to identify factors associated with having symptoms. Race did not meet criteria for model entry. Results/Outcomes: (1) 154 of 275 (56%) offenders reported ongoing TBI-related symptoms. (2) SuD and PTSD were associated with having symptoms. An interaction was found between SuD and PTSD (p=0.0236). (3) An association was further found between females with PTSD and TBI-related symptoms among those without SuD (adjusted prevalence ratio (APR)=2.58; CI 1.49 to 4.45, p=0.0006), but not among those with SuD (APR=1.30; CI 0.98 to 1.73, p=0.0662). (4) Compared to having neither condition, the APR for the association between SuD and TBI-related symptoms was 2.32 (CI 1.34 to 4.01). The APR for the association with TBI-related symptoms among offenders with both SuD and PTSD, compared to having neither, was 3.03 (CI 1.80 to 5.08). Significance/Contribution to the Field: PTSD and SuD are closely associated with ongoing TBI-related symptoms. Treating and managing all three conditions concurrently, as well as prevention efforts, would likely be cost effective and benefit both the female offenders and society.